41. EXAMINATION OF THE MEKONG DELTA REGION’S PHYSICAL HUMAN RESOURCES CURRENT STATUS IN 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze the current status of the distribution and structure of the pharmacy workforce in the Mekong delta region of Vietnam.Methods: A cross-sectional descriptive study was conducted, surveying 2614 pharmacy personnel working at 133 public general hospitals in the Mekong delta region as of December 31, 2022.Results: University-educated pharmacists constituted 46.6% of the workforce, while personnel with college and intermediate diplomas in pharmacy accounted for 53.1%, and pharmacy assistants comprised approximately 0.3%. A marked disparity was observed in the pharmacy workforce structure among provinces, as well as between urban and rural areas. In the majority of the region’s provinces, the ratios of pharmacists/college and intermediate diplomas in pharmacy, pharmacists to physicians, and pharmacists to hospital beds fell below the benchmarks stipulated in Circular 03/2023/TT-BYT. The distribution of pharmacists across general hospitals was also inequitable, with an average of only 6.8 pharmacists per hospital. Notably, 18 hospitals (13.5%) were found to have no pharmacists on staff.Conclusion: In the Mekong delta region, the proportion of pharmacists is low, with the workforce being predominantly composed of college and intermediate diplomas in pharmacy. A significant imbalance in the pharmacy workforce structure persists between urban and rural areas. Furthermore, the ratios of pharmacists to hospital beds, physicians, and per hospital remain at critically low levels.
Keywords: Thực trạng, nhân lực dược; bệnh viện đa khoa; đồng bằng sông Cửu Long.